Empowering Youth through Play : Promoting Awareness of Sexual Grooming among Schoolchildren through Game-based Learning - Ally Dian, Hendrick; Amelia Jati, Robert Jupit; A. Imran, Nordin (Semarak Ilmu Publishing, 2025)
Sexual grooming is engaging with a child to build a relationship with intentions of sexual exploitation. In some cases, it precedes child sexual abuse. The need for child sex education can be further illustrated by the severity of the trauma that results from the abuse. Hence, it is ideal to recognise the signs of grooming to reduce the risk of child sexual grooming. This project aims to develop an age-appropriate game to assess game-based learning to educate children on preventing sexual grooming. The methodology implemented in this project is the outcome-based methodology. First, a survey was distributed to guide the design of the game and to identify the relevant learning outcomes relating to sex education the respondents wish their children to learn. Based on the results, there are four learning outcomes to be achieved. Second, the genre of the game was determined to be a visual novel. Third, the premise of the game was written. Fourth, assets to enhance the playing experience were either created or sourced online. Fifth, the game mechanics were developed using Godot Engine. Sixth, the game mechanics were play tested iteratively, before and after integration with one another. Seventh, all the mechanics and non-mechanic elements were integrated to complete development. Eighth, the game was play tested online. Pre- and post-test results from the playtest were recorded and evaluated. Using paired samples t-test with a 95% confidence interval, the calculated t-value 12.011 was more significant than the critical t-value of 2.042, and the p-value 0.00001 was lesser than the significance level of 0.05. The result suggests that using the game to create awareness of physical and online grooming towards children was effective.